The Nature of The Application of Legal Justice to The Systematics of Land Registration According to Government Regulation Number 24 of 1997 - Reza Zulfikar, Muhammad (Manunggal Halim Jaya, 2024)
This research aims to explore the principles of legal justice that should be applied in the process of land registration in Indonesia by analyzing whether Law No. 24 of 1997 can successfully create a fair system for all parties. a qualitative approach with normative analysis, this research outlines the various aspects of justice that should be reflected in the law. Research Result, creating a fair and equitable land registration system, there are still various technical, administrative, and social obstacles that hinder the realization of optimal application of the principles of justice. Conclusion in terms of land registration policies and practices to ensure legal justice can be realized more effectively and equitably for all Indonesian people.